2021
DOI: 10.3928/1081597x-20201123-03
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-up of Intracorneal Ring Segments Implantation in Adolescent Patients With Keratoconus

Abstract: PURPOSE: To evaluate the visual, refractive, topographic, and aberrometric outcomes after intracorneal ring segments (ICRS) implantation in adolescent patients with keratoconus. METHODS: A retrospective longitudinal study was undertaken with a total of 61 eyes from 47 patients with keratoconus, aged between 13 and 18 years, implanted with a Ferrara-type ICRS. Topography (flattest keratometry, steepest keratometry, and asphericity), uncorrected distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…The vertical coma was only significantly different at 2 years postoperatively. Therefore, ICRS implantation is a safe and effective treatment to improve the visual and morphological parameters of the cornea, as demonstrated in 2 years of follow-up in adolescent patients with KC [19].…”
Section: Major Findingsmentioning
confidence: 96%
“…The vertical coma was only significantly different at 2 years postoperatively. Therefore, ICRS implantation is a safe and effective treatment to improve the visual and morphological parameters of the cornea, as demonstrated in 2 years of follow-up in adolescent patients with KC [19].…”
Section: Major Findingsmentioning
confidence: 96%
“…So far, ICRS has been shown to be an effective method in managing keratoconus, with many recent studies reporting a significant improvement in UDVA, CDVA, refraction, and keratometric readings (Table 3) (159,(167)(168)(169)(170)(171)(172)(173)(174)(175). In a sizeable multicentered study of 611 eyes with varying degree of keratoconus, Vega-Estrada et al (176) observed a significant improvement in UDVA in all cases of keratoconus and CDVA in the majority of cases (except for mild keratoconus with 0.1 logMAR vision or better).…”
Section: Intracorneal Ring Segmentsmentioning
confidence: 99%
“…O implante de ICRS é uma opção cirúrgica segura, eficaz, reversível e ajustável para o tratamento do ceratocone, com resultados variáveis dependentes das diferentes experiências entre cirurgiões e unidades [49][50][51][52][53][54][55] . O implante de ICRS atua reduzindo o erro esférico-cilíndrico por modificação induzida na curvatura central da córnea e redução das aberrações de alta ordem conseguidas pela regularização da superfície da córnea 56 .…”
Section: Introductionunclassified